ANALYSIS OF THE CRIME OF MOTORCYCLE THEFT COMMITTED BY A CHILD (A Study of Decision Number 7/Pid.Sus-Anak/2017/PN Pga) - Haka; Rahmayanti; Redyanto Sidi (CV. RADJA PUBLIKA, 2025)
This study examines juvenile motorcycle theft based on Court Decision No. 7/Pid.Sus-Anak/2017/PN Pga, prompted by the increasing involvement of minors in such crimes. It addresses factors contributing to juvenile offenses, the law enforcement process, and the legal policy applied in the decision. Utilizing a normative juridical method with statutory, conceptual, and case approaches, this research qualitatively analyzes primary, secondary, and tertiary legal materials. Results reveal that economic hardship, insufficient moral and religious education, negative social environments, and weak family supervision are key contributing factors. In enforcement, Law No. 11 of 2012 on the Juvenile Criminal Justice System was applied, upholding child protection principles. The judge's legal policy, prioritizing the child's best interest, sentenced the offender to 10 months in prison, acknowledging remorse and rehabilitation needs. Conclusively, the juvenile justice system should emphasize restorative over repressive approaches. Recommendations urge active roles from government, society, and families in preventing juvenile delinquency through continuous moral education, supervision, and guidance.